The Effectiveness of the Psychosocial Trauma Healing Learning Model in Enhancing the Learning Interest of Elementary School Children Post-Flood in Langkat - Uswatun Hasanah; Wahyu Hidayat (Jurnal Penelitian Medan Agama, 2026)
Flooding is one of the most frequent disasters occurring in Langkat Regency, North Sumatra, causing not only physical damage but also psychological impacts on elementary school children. This study aimed to analyze the effectiveness of a psychosocial trauma healing learning model in improving learning interest among elementary school children after flooding in Perdamaian Village, Langkat Regency, North Sumatra. A quasi-experimental study with a one-group pretest-posttest design was employed. The sample consisted of 50 flood-affected elementary school students selected through purposive sampling. The intervention was conducted for four weeks through play therapy, storytelling, art therapy, educational games, group reflection, and experiential learning activities. Data were collected using a learning interest questionnaire and observation sheets. Data were analyzed using a Paired Sample t-Test. The results showed that the mean learning interest score increased from 60.42±8.15 before intervention to 81.76±7.28 after intervention with p=0.01 (p<0.05). These findings indicate that the psychosocial trauma healing learning model effectively improves students' learning interest by restoring emotional well-being, enhancing feelings of safety, and creating an enjoyable learning environment. This model is recommended as an educational recovery strategy for elementary school children after disasters.